Active Learning Training with Mathematics Tools at SD HKBP Pembangunan 3 Medan - Siringoringo, Yan Batara Putra; Nababan, Esther Sorta Mauli; Manurung, Asima; Marbun, James Piter; Napitupulu, Normalina; Marpaung, J.L. (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Education is an attempt by the Government to increase the country's potential to be able to compete with other countries that are experiencing very rapid development. The development of education will have an influence on the life of the local community, that is, it can affect various aspects of life, be it social, economic, cultural, religious, language and also the environment. The extent of the influence of educational development on aspects of life can be studied independently. Besides that, education also plays a major role in expanding employment opportunities, encouraging activities of supporting industries, introducing natural and cultural beauty that is inseparable from a sense of increasing brotherhood in the national and international environment. This is because education itself creates multiple economic impacts, namely direct, indirect, and secondary impacts, which provide opportunities for the growth of businesses and the role of local communities in the education sector. This research will discuss about Active Learning Training with Mathematics Tools at SDS HKBP Pembangunan 3 Medan. The result achieved is that schools are able to provide effective services online in the face of changing times caused by Covid-19 and can provide more information regarding the location of tourist objects that will be traversed by local and foreign tourists.